Assessing Boundary Conditions of the Testing Effect: On the Relative Efficacy of Covert vs. Overt Retrieval - Sundqvist, Max L.; Mäntylä, Timo; Jönsson, Fredrik U. (Frontiers in Psychology, 2017)
Repeated testing during learning often improves later memory, which is often referred to as the testing effect. To clarify its boundary conditions, we examined whether the testing effect was selectively affected by covert (retrieved but not articulated) or overt (retrieved and articulated) response format. In Experiments 1 and 2, we compared immediate (5 min) and delayed (1 week) cued recall for paired associates following study-only, covert, and overt conditions, including two types of overt articulation (typing and writing). A clear testing effect was observed in both experiments, but with no selective effects of response format. In Experiments 3 and 4, we compared covert and overt retrieval under blocked and random list orders. The effect sizes were small in both experiments, but there was a significant effect of response format, with overt retrieval showing better final recall performance than covert retrieval. There were no significant effects of blocked versus random list orders with respect to the testing effect produced. Taken together, these findings suggest that, under specific circumstances, overt retrieval may lead to a greater testing effect than that of covert retrieval, but because of small effect sizes, it appears that the testing effect is mainly the result of retrieval processes and that articulation has fairly little to add to its magnitude in a paired-associates learning paradigm.